1998
DOI: 10.1210/en.139.5.2414
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Regulation of the Rat Proopiomelanocortin Gene Expression in AtT-20 Cells

Abstract: Although cytokines are known to be involved in the regulation of ACTH secretion, their effects, along with the molecular mechanisms, on POMC gene expression are not thoroughly characterized. In this study we examined the effects of representative cytokines on transcription of the POMC gene in corticotrophs in vitro using AtT20PL, a clone of the AtT20 cell line stably transfected with approximately 0.7 kilobase of the rat POMC 5'-promoter-luciferase fusion gene. In each experiment, cells were incubated with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
29
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 0 publications
7
29
0
Order By: Relevance
“…Hypothetically, the intrapituitary proinflammatory cytokines IL-6 or IL-1, which are rapidly produced after a peripheral LPS challenge by folliculostellate cells [28], could regulate the IL-6R component in corticotropes. Such a necessary upregulation of IL-6R complex in the pituitary is in accordance with the long-term effect of IL-6 on ACTH secretion measured in vitro [7, 15, 16, 17]. …”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Hypothetically, the intrapituitary proinflammatory cytokines IL-6 or IL-1, which are rapidly produced after a peripheral LPS challenge by folliculostellate cells [28], could regulate the IL-6R component in corticotropes. Such a necessary upregulation of IL-6R complex in the pituitary is in accordance with the long-term effect of IL-6 on ACTH secretion measured in vitro [7, 15, 16, 17]. …”
Section: Discussionsupporting
confidence: 77%
“…We demonstrated that SOCS-3 mRNA is rapidly induced (within 2 h) in corticotropes during peripheral inflammation. It has been reported that in vivo, LPS-induced SOCS-3 mRNA in mice was concordant with a rapid ACTH release (1–4 h) [30], whereas the effect of IL-6 on ACTH release in vitro generally occurs only after several hours of incubation [7, 15, 16, 17]. The rapid effect of IL-6 on ACTH release could be linked to IL-6 control of exocytosis, but no data are currently available.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations